Gut microbiota development in very preterm infants following fortification of human milk - Lin Yang; Yan Hui; Per Torp Sangild; Witold Piotr Kot; Lise Aunsholt; Gitte Zachariassen; Ping-Ping Jiang; Dennis Sandris Nielsen (mSystems)
ABSTRACT Very preterm infants (VPIs) are born with an immature gut and predisposed to gut microbiota dysbiosis-related diseases, for example, necrotizing enterocolitis. Although fortification of human milk is required for these infants, the optimal fortifier remains uncertain. Bovine colostrum (BC), rich in protein and bioactive components, could serve as an alternative to conventional fortifiers (CF). The gut microbiota (GM) of 225 VPIs fed human milk fortified with either BC or CF (FortiColos study, NCT03537365) was profiled by 16S rRNA gene amplicon sequencing of fecal samples collected before, and after 1 and 2 weeks of fortification. Birth mode exhibited transient effects on the microbial community structure shortly after birth, with cesarean section-born VPIs dominated by Firmicutes, whereas vaginally born VPIs were dominated by Proteobacteria. This birth mode-derived difference diminished with age and disappeared around 1 month after birth. Fortifier type affected the microbial community structure to a modest extent, but no specific taxa significantly differed between the BC and CF groups. Fecal pH, increased by BC, was positively correlated with Staphylococcus and Corynebacterium and negatively with Bifidobacterium abundance. Change in the relative abundance of Staphylococcus was negatively correlated with body weight gain. Collectively, fortification of human milk with BC or CF does influence the GM of VPIs but only to a modest extent during early life. Birth mode appears to have a significant, but temporary influence on the GM during this period.IMPORTANCEEarly life is a key period for gut microbiota (GM) establishment, where enteral feeding plays a significant role. This is also the case for infants born preterm, who, due to their immature gut, are at a high risk of developing GM dysbiosis-related diseases. Human milk is the optimal feed for preterm infants, but it requires fortification to reach adequate levels of especially protein. Only a few studies have investigated the impact of fortifiers on GM development in preterm infants. Here, we demonstrate that two different bovine milk-based fortifiers, bovine colostrum and a conventional fortifier based on mature bovine milk, exhibit limited effects on the microbial community structure of very preterm infants. These findings suggest that although great care in terms of optimally maturing the preterm infant GM should be taken, the choice of fortifier only has limited impact. In clinical practice, the choice of fortifier can thus be fully focussed on optimizing preterm infant nutrition.CLINICAL TRIALSThis study is registered with ClinicalTrials.gov as NCT03537365.